OUTSIDE REARVIEW MIRROR PANORAMIC CAMERA POSITION ON THE AERODYNAMIC CHARACTERISTICS OF IMPACT STUDY - TONG GaoPeng; GAN Wei; LI ZhiWei; LIN Hui; WANG ZhiFeng (Jixie qiangdu)
In order to reduce the influence of the panorama camera on the aerodynamic noise of the vehicle,the exterior flow field and sound field analysis are carried out on the rearview mirror of three different lens placement positions.The calculated results are in good agreement with the experimental data,which verifies the reliability of the numerical simulation.At the same time,it is found that the different position of the panoramic lens has an influence on the air flow which through the exterior mirrors,thus changing the rear flow field and the front window noise radiation intensity.Scheme Ⅲ is compared with other schemes,the tail vortex,the turbulence kinetic energy and the noise emission of the front window are relatively weaker,which can reduce the aerodynamic noise.Finally,by comparing the noise test of three kinds of schemes,it is found that the noise of scheme Ⅲ is lower than that of other schemes,which verifies the correctness of the analysis method.The analysis results provides the guidance for the reasonable arrangement of the rearview mirror panorama image lens,and is favorable for improving the comfort of the driver.